Development and Evaluation of a Prototype of Learning Support System for Honorific Forms in Japanese - Nakayama, Minoru; Morita, Keisuke (International Journal of Advanced Corporate Learning (iJAC), 2009)
Most Japanese encounter difficulty using the honorific form. A prototype of a web-based learning support system for Japanese honorific forms was developed in response to the results of a needs assessment survey. Using the results garnered from this study, learning performance and its interaction with learnersâ?? characteristics was examined. Initial results suggests that by using this prototype tool, learners have gained mastery in assessing the situations they are engaged in, thus leading them to use honorific forms more correctly.